2017
DOI: 10.1038/jes.2016.79
|View full text |Cite
|
Sign up to set email alerts
|

Residential proximity to abandoned uranium mines and serum inflammatory potential in chronically exposed Navajo communities

Abstract: Members of the Navajo Nation, who possess a high prevalence of cardiometabolic disease, reside near hundreds of local abandoned uranium mines (AUM), which contribute uranium, arsenic and other metals to the soil, water and air. We recently reported that hypertension is associated with mine waste exposures in this population. Inflammation is a major player in the development of numerous vascular ailments. Our previous work establishing that specific transcriptional responses of cultured endothelial cells treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 35 publications
2
40
0
Order By: Relevance
“…Studies linking non-occupational uranium exposure to cardiovascular disease provide supportive evidence for our findings without establishing causality (41). A recent study highlighted the effects of inhalational environmental uranium exposure on cardiovascular disease outcomes among Navajo community members who live in close proximity to abandoned uranium mines in NM (41).…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Studies linking non-occupational uranium exposure to cardiovascular disease provide supportive evidence for our findings without establishing causality (41). A recent study highlighted the effects of inhalational environmental uranium exposure on cardiovascular disease outcomes among Navajo community members who live in close proximity to abandoned uranium mines in NM (41).…”
Section: Discussionsupporting
confidence: 69%
“…Studies linking non-occupational uranium exposure to cardiovascular disease provide supportive evidence for our findings without establishing causality (41). A recent study highlighted the effects of inhalational environmental uranium exposure on cardiovascular disease outcomes among Navajo community members who live in close proximity to abandoned uranium mines in NM (41). Primary human coronary artery endothelial cells treated for 4 hours with serum provided by Navajo study participants revealed that proximity to abandoned uranium mine strongly predicted endothelial transcriptional responses to serum cell adhesion molecules and chemokines (including CCL2, VCAM-1, and ICAM-1), suggesting inflammatory potential associated with residential proximity to abandoned uranium mines (41).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The mined regions are contaminated with arsenic, copper, uranium, and other heavy metals as well as remaining radionuclides, representing an exposure risk to metals associated with adverse health and developmental effects [ 2 ]. Harmon et al (2017 and 2018) reported an association between arsenic and uranium from water intake and residential proximity to abandoned uranium mining sites with markers of pre-clinical cardiovascular effects [ 3 , 4 ]. In a recent review, Gonzales et al (2018) identified Native American and other rural populations in the Southwest, Mountain West, and adjacent regions of the U.S. to be at risk for sufficient exposure to environmental metals to result in elevated risks for numerous adverse health outcomes [ 5 ].…”
Section: Introductionmentioning
confidence: 99%